2002
DOI: 10.1128/mcb.22.15.5380-5394.2002
|View full text |Cite
|
Sign up to set email alerts
|

The UV (Ribotoxic) Stress Response of Human Keratinocytes Involves the Unexpected Uncoupling of the Ras-Extracellular Signal-Regulated Kinase Signaling Cascade from the Activated Epidermal Growth Factor Receptor

Abstract: In mammals, UVB radiation is of biological relevance primarily for the cells of the epidermis. We report here the existence of a UVB response that is specific for proliferating human epidermal keratinocytes. Unlike other cell types that also display a UVB response, keratinocytes respond to UVB irradiation with a transient but potent downregulation of the Ras-extracellular signal-regulated kinase (ERK) signaling cascade. The downregulation of ERK precedes a profound decrease in the steady-state levels of cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 80 publications
7
73
1
1
Order By: Relevance
“…JNK pathways are also involved in the phosphorylation and activation of several transcription factors, including c-Jun (Derijard et al, 1994), ATF-2 (Read et al, 1997), Elk-1 (Cavigelli et al, 1995), and p53 (Milne et al, 1995). Studies have demonstrated that cell exposure to UV irradiation causes activation of the MAPK pathway (Chen et al, 2002;Chouinard et al, 2002;Iordanov et al, 2002;She et al, 2002). JNK1/2 and p38 kinases are potently activated by various forms of stress, such as UV, heat shock, and inflammation Figure 7 Inhibitory effect of green tea polyphenol on UVBinduced activation of IKKa, and phosphorylation and degradation of IkBa in SKH-1 hairless mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JNK pathways are also involved in the phosphorylation and activation of several transcription factors, including c-Jun (Derijard et al, 1994), ATF-2 (Read et al, 1997), Elk-1 (Cavigelli et al, 1995), and p53 (Milne et al, 1995). Studies have demonstrated that cell exposure to UV irradiation causes activation of the MAPK pathway (Chen et al, 2002;Chouinard et al, 2002;Iordanov et al, 2002;She et al, 2002). JNK1/2 and p38 kinases are potently activated by various forms of stress, such as UV, heat shock, and inflammation Figure 7 Inhibitory effect of green tea polyphenol on UVBinduced activation of IKKa, and phosphorylation and degradation of IkBa in SKH-1 hairless mice.…”
Section: Discussionmentioning
confidence: 99%
“…of 12 mice (*Po0.001 vs UVB). ns, nonspecific Suppression of UVB effects in mouse skin by GTP F Afaq et al (Derijard et al, 1994;Chen et al, 2002;Chouinard et al, 2002;Iordanov et al, 2002). Experimental studies have shown that ERK1/2 and p38 are involved in the transcriptional activation of NF-kB (Adderley and Fitzgerald, 1999;Carter et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The spectral characterization of the UV-B source and the mode of the irradiation of cells with UV-B are described in ref. 13. Proteasome inhibitor MG-132 was from Calbiochem.…”
Section: Methodsmentioning
confidence: 99%
“…Inflammation in the Skin-We have previously reported that the basal levels of ERK activity in HEKn or HEKn-E6/E7 in tissue culture were determined by the autocrine secretion of ligands that bind to the EGFR (20). Interfering with either the extracellular ligand-binding portion of EGFR by means of the LA-1 antibody or the intracellular kinase domain of EGFR reduced the basal phosphorylation of ERK1 and ERK2 to undetectable levels (20).…”
Section: A Novel Role Of the Egfr-ras-erk Cascade In Mediatingmentioning
confidence: 99%
“…were established and propagated as described (20,21). For RHE, we employed the method of Poumay et al (22), with modifications as described in Ref.…”
Section: Rhe: Primary Human Epidermal Keratinocytes (Neonatal) (Hekn)mentioning
confidence: 99%